2016
DOI: 10.2216/15-11.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular characterization ofUlva chaugulii sp. nov.,U. lactucaandU. ohnoi(Ulvophyceae, Chlorophyta) from India

Abstract: Morphological and molecular characterization ofUlva chaugulii sp. nov., U. lactuca and U. ohnoi (Ulvophyceae, Chlorophyta) from India M ud a ssa r A n iso d d in K a z i', M o n ic a G. K a v a l e '* a n d V e e r e n d r a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 29 publications
(4 reference statements)
0
25
0
12
Order By: Relevance
“…Distribution. Korea (Bae 2010, Kim et al 2013); Japan ; America (Melton et al 2016, Chávez-Sánchez et al 2018; Southwest Asia (Kazi et al 2016, Krupnik et al 2018; Australia and New Zealand (Kirkendale et al 2013);Pacific Islands (O'Kelly et al 2010); Africa (Miladi et al 2018); Europe (Miladi et al 2018).…”
Section: Ulva Ohnoi M Hiraoka and S Shimada 2003 P 20 Figsmentioning
confidence: 99%
“…Distribution. Korea (Bae 2010, Kim et al 2013); Japan ; America (Melton et al 2016, Chávez-Sánchez et al 2018; Southwest Asia (Kazi et al 2016, Krupnik et al 2018; Australia and New Zealand (Kirkendale et al 2013);Pacific Islands (O'Kelly et al 2010); Africa (Miladi et al 2018); Europe (Miladi et al 2018).…”
Section: Ulva Ohnoi M Hiraoka and S Shimada 2003 P 20 Figsmentioning
confidence: 99%
“…The study also showed the separate species position for the Indian specimen of C. peltata [81]. The DNA taxonomy also helped in identifying two new species of genus Ulva, U. chaugulii [82] and U. paschima [83] from Indian shores. However, U. paschima is now regarded as synonym of U. tepida [16].…”
Section: Developing Integrated Taxonomymentioning
confidence: 98%
“…Этот вид был описан из Японии (Hiraoka et al, 2004), где его экземпляры были обнаружены в виде свободно плавающих талломов, вызывающих «зеленые» приливы. Этот вид также был зарегистрирован в последние годы в разных странах Карибского моря (Melton et al, 2016), в Средиземном море (Miladi et al, 2018), Иране (Pirian et al, 2016), Индии (Kazi et al, 2016) и Восточной Австралии (Lawton et al, 2013). На побережье Карачи мы не выявили свободно плавающих экземпляров, все они были обнаружены на берегу среди приносимого прибоем мусора.…”
Section: цитологические особенностиunclassified
“…Морфология изученных экземпляров (зубчатый край таллома, клетки на поверхности прямоугольной до гексагональной формы, положение содержимого хлоропласта на поперечном сечении таллома) схожа с японской U. ohnoi. Ризоидальный диск с небольшой ножкой также отмечали Kazi et al (2016). Строение хлоропласта вблизи базальной части таллома отличается от известного ранее.…”
Section: цитологические особенностиunclassified